THE CHALLENGE OF CRITICAL EDUCATION - Sultanan, Ronald G. (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1991)
This article looks at the theory and practice of critical education, situating this within its philosophical context and exploring the contribution it makes to the understanding of the structures, curricula, culture, and pedagogy of schooling. The author concludes by drawing on the work of Habermas to examine possibilities and constraints in the attempt to develop a truly democratic and dialogic educational practice. RÉSUMÉ Dans cet article, l’auteur analyse la théorie et la pratique de l’éducation critique, la situant dans son contexte philosophique et s’interrogeant sur sa contribution à la compréhension des structures, des programmes, de la culture et de la pédagogie scolaires. L’auteur s’inspire des oeuvres de Habermas pour étudier les possibilités et les limites qui s’opposent au développement d’un enseignement véritablement démocratique et fondé sur le dialogue.